A Proposal for Improving Reading Comprehension Skills of Gifted Students:An Analytic Writing and Assessment Model Integrated with Intertextual Reading - Bilge Gök; Abdulkadir Sağlam (e-Kafkas Eğitim Araştırmaları Dergisi)
It is observed that research on gifted students mainly focuses on issues such as reading habits and attitudes towards reading. It is important to develop the reading comprehension skills of these students and it is necessary to implement new strategies to improve the reading comprehension skills of gifted students. The purpose of this research is to uncover the impact of the 6+1 Analytical Writing and Evaluation Model (AWEM), when combined with intertextual reading, on the reading comprehension abilities of gifted students. The study employed a four-group semi-experimental design within the framework of quantitative research methodologies. The participant cohort comprised 28 gifted fourth-grade students. Over a span of 7 weeks, the experimental phase of the study aligned with the sub-dimensions of the 6+1 AWEM. Data were collected using the Intertextuality Reading Comprehension Test (IRCT), and subsequently analyzed utilizing the paired samples t-test. The findings revealed a positive correlation between the integration of intertextual reading and the 6+1 AWEM, and the enhancement of reading comprehension skills among gifted students. Furthermore, the experimental activities centered around intertextuality and the 6+1 AWEM Model were found to have a positive impact on the sustained levels of reading comprehension proficiency among the gifted students. Another notable outcome of the study was the affirmative influence of the experimental activities involving the 6+1 AWEM, combined with intertextual reading, on the enduring improvement of reading comprehension levels in fourth-grade gifted students.